Effect of PGF2α and Methylergometrine during Puerperium in Gir Cows - Solanki, GB; Chaudhary, JK; Vijyeta, HP; Gamit, PM; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The therapeutic efficacy of methylergometrine and PGF2α on uterine involution and postpartum fertility was studied in 18 (6/group) Gir cows. Animals of groups I and II were treated with single i/m injection of PGF2α and Methylergometrine immediately after parturition, respectively, while group-III served as untreated control. The time required for expulsion of fetal membranes was shorter in group-I (2.55 ± 0.60 hours) than in group II (3.03 ± 0.34 hours) and group III (4.10 ± 0.36 hours) but did not differ statistically. Time taken for completion of uterine involution was significantly (p <0.05) shorter in group I (28.67±1.12 days) than that of group II (35.83 ± 1.49 days) and group-III (41.00±1.46 days). The intervals for first estrus postpartum and service period were also significantly (p <0.01) shorter for group I (37.83 ± 1.10 and 89.50 ± 4.34 days) than in group-II (46.17 ± 1.40 and 108.33 ± 4.91 days) and group-III (50.83 ± 1.11 and 118.33 ± 4.40 days, respectively). The number of services per conception was non-significantly lower in group I (1.17 ± 0.17) as compared to group II (1.50 ± 0.34) and controlled group III (1.67±0.33). The conception rate was 100% in group I and 83.33 % each in group II and III. Thus, it can be concluded that use of PGF2α immediately after parturition in Gir cows enhanced the process of placental separation, hastened the uterine involution, decreased the service period, increased the conception rate and thereby reduce the calving interval to the profitable ambiance as compared to Methylergometrine and control groups.